Powierzchnie Graniczne dla Niejednorodnych Powłok Obrotowych - Sankaranarayanan, R. (Engineering Transactions, 1966)
The state of stress in a rotationally symmetric shell is characterized by the direct stresses and moments in the circumferential and longitudinal directions. It is assumed that the material of the shell is rigid perfectly plastic and that the yield stress of the material varies over the thickness of the shell. The yield condition for the shell is obtained in terms of the stress resultants assuming that the material of the shell obeys the maximum shear stress criterion.